Lulur Gosok Tradisional BERSERI (Beras, Serai Wangi, Kunyit) sebagai Antioksidan - Rahmadevi Rahmadevi; Fitriani Arin; Oktaviani Puspita; Armayana Firda; Yasnawati Yasnawati (Jurnal Abdimas Kesehatan (JAK), 2020)
Traditional body scrubis one cosmetic sedian that is made from fresh natural or ingredients that have been dried from plants and fruit. The basic ingredient of making scrubs commonly used in traditional cosmetics is rice flour. Rice has a rich content of protein, vitamins, minerals and water. The content found in rice flour is gamma oryzanol. And this compound can renew the formation of melanin pigment, as an antioxidant and also effective to ward off ultrafiolet rays. Besides turmeric also has activity as an antioxidant derived from kukumin contained in turmeric. Lemongrass also gives romatherapy to the body scrub because it contains essential oils which give a distinctive odor. The purpose of this research is to increase the knowledge of the women of Lubuk Dalam Hamlet on Traditional Scrub Scrub derived from rice and spices such as turmeric which has antioxidant activity and Lemongrass that can give aromatherapy to the scrub. This community service method uses a participatory method that involves the community of Kemingking Dalam Village. The results of this study found that the increased knowledge of the community of Kemingking Dalam Village regarding the efficacy and ways of making scrubs derived from rice, turmeric and lemongrass